Design Study on Ship Based Small Nuclear Power Reactors - Zaki Su'ud; Dian Fitriyani (Institut Teknologi Bandung, 2004)
The results of conceptual design study on ship based small nuclear power reactors are presented. The reactors are basically lead-bismuth cooled fast power reactors with long refueling interval and low reactivity swing. Here we optimized the designs to achieve the feasibility to be operated under sea wave movement. The system use loop type with relatively large coolant pipe above reactor core. The reactors do not use IHX, so that the heat from primary coolant system directly transferred to water-steam loop through steam generator. The reactors are capable to be operated in difference power level during night and noon. This feature is necessary because in some rural area the main use of the reactors is just to support home electricity. The reactors however can also be used totally or partially to produce clean water through desalination of seawater. Due to the influence of sea wave movement the analysis have to be performed in three dimensional analysis. We found that the effect of the seawater movement is significant in changing flow pattern distribution and outlet temperature distribution.